Cost-effectiveness of the fixed-dose combination tiotropium/olodaterol versus tiotropium monotherapy or a fixed-dose combination of long-acting β2-agonist/inhaled corticosteroid for COPD in Finland, Sweden and the Netherlands: a model-based study. Issue 8 (4th August 2021) - Hoogendoorn, Martine; Corro Ramos, Isaac; Soulard, Stéphane; Cook, Jennifer; Soini, Erkki; Paulsson, Emma; Rutten-van Mölken, Maureen
Abstract : Objectives: Chronic obstructive pulmonary disease (COPD) guidelines advocate treatment with combinations of long-acting bronchodilators for patients with COPD who have persistent symptoms or continue to have exacerbations while using a single bronchodilator. This study assessed the cost-utility of the fixed dose combination of the bronchodilators tiotropium and olodaterol versus two comparators, tiotropium monotherapy and long-acting β2 agonist/inhaled corticosteroid (LABA/ICS) combinations, in three European countries: Finland, Sweden and the Netherlands. Methods: A previously published COPD patient-level discrete event simulation model was updated with most recent evidence to estimate lifetime quality-adjusted life years (QALYs) and costs for COPD patients receiving either tiotropium/olodaterol, tiotropium monotherapy or LABA/ICS. Treatment efficacy covered impact on trough forced expiratory volume in 1 s (FEV1 ), total and severe exacerbations and pneumonias. The unit costs of medication, maintenance treatment, exacerbations and pneumonias were obtained for each country. The country-specific analyses adhered to the Finnish, Swedish and Dutch pharmacoeconomic guidelines, respectively. Results: Treatment with tiotropium/olodaterol gained QALYs ranging from 0.09 (Finland and Sweden) to 0.11 (the Netherlands) versus tiotropium and 0.23 (Finland and Sweden) to 0.28 (the Netherlands) versus LABA/ICS. The Finnish payer's incremental cost-effectiveness ratio (ICER) of tiotropium/olodaterol was €11 000/QALY versus tiotropium and dominant versus LABA/ICS. The Swedish ICERs were €6200/QALY and dominant, respectively (societal perspective). The Dutch ICERs were €14 400 and €9200, respectively (societal perspective). The probability that tiotropium/olodaterol was cost-effective compared with tiotropium at the country-specific (unofficial) threshold values for the maximum willingness to pay for a QALY was 84% for Finland, 98% for Sweden and 99% for the Netherlands. Compared with LABA/ICS, this probability was 100% for all three countries. Conclusions: Based on the simulations, tiotropium/olodaterol is a cost-effective treatment option versus tiotropium or LABA/ICS in all three countries. In both Finland and Sweden, tiotropium/olodaterol is more effective and cost saving (ie, dominant) in comparison with LABA/ICS.